Implementation of 2% Chlorhexidine Bathing to Reduce Healthcare-Associated Infections Among Patients in the Intensive Care Unit - Hsu-Liang Chang; Tzu-Ying Liu; Po-Shou Huang; Chin-Hwan Chen; Chia-Wen Yen; Hui-Zhu Chen; Shin-Huei Kuo; Tun-Chieh Chen; Shang-Yi Lin; Po-Liang Lu (Microorganisms)
Healthcare-associated infections (HAIs) significantly increase morbidity, mortality, length of hospital stays, and costs, particularly among ICU patients. Despite standard interventions, catheter-associated urinary tract infections (CAUTI) and central line-associated bloodstream infections (CLABSI) remain major HAI contributors. This study evaluated the efficacy of daily 2% chlorhexidine gluconate (CHG) bathing in reducing HAI incidence, specifically CAUTI, CLABSI, and multidrug-resistant organisms (MDROs), in a 20-bed ICU at a regional hospital. Using a prospective, uncontrolled before-and-after design, we compared traditional soap-water bathing (pre-intervention period) with CHG bathing over a one-year intervention and one-year post-intervention follow-up. The total number of patients and patient days admitted to the ICU per year were around 1330–1412 patients and 6702–6927 patient days, respectively, during 2018–2020. Results showed a significant reduction in HAI incidence rates from 3.43‰ to 0.58‰ (p < 0.05) during the intervention and sustained benefits post-intervention. Incidences of CAUTI and CLABSI decreased markedly (p < 0.05), with reduced MDRO isolates, including methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococci, carbapenem-resistant Acinetobacter baumannii, and Pseudomonas aeruginosa. Our findings support the implementation of daily CHG bathing as an effective strategy to reduce HAI and MDROs in ICU settings.